The Transformation of Noken Papua: Understanding the Dynamics of Noken’s Commodification as the Impact of UNESCO’s Heritage Recognition - Salhuteru, Alice; Hutubessy, Fred Keith (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
This research was motivated by previous studies that discussed Noken from various points of view but did not examine aspects of the commodification of Noken as an implication of the world heritage label from UNESCO. Noken is a native Papuan knit bag that has high cultural values, sacred entity, and a source of life; as a container for carrying garden products and animal hunting products. Noken is also a form of maturity initiation, Papuan woman who can knit noken may enter the marriage phase. Applying the qualitative method, with observations and interviews with women knitting and selling it in Jayapura as informants, this study found that: firstly, Noken had undergone massive economic commodification, started with UNESCO's recognition of inherited noken as intangible, which led to more and more traded noken. Secondly, noken has transformed values, especially about the noken value that animates them. The transformation of values in noken is a necessity in the dynamics of the social, economic, and cultural changes of the Papuan. Thirdly, by knitting and selling it, they are trying to preserve the sacred value of noken, also as a strategy to survive economically in encountering the impact of the capitalist system.